2015
DOI: 10.1111/bcp.12641
|View full text |Cite
|
Sign up to set email alerts
|

Statins are associated with a reduced risk of cholangiocarcinoma: a population‐based case–control study

Abstract: Aims Cholangiocarcinoma (CCA) is the second most common primary liver cancer in the world. Due to the lack of effective treatments, the survival rate of CCA is low and it is usually considered difficult to diagnose early. To date, no effective strategies for the prevention of CCA have been developed. Statins are cholesterol‐lowering agents which possess pleiotropic properties and the use of statins may reduce cancer risk. The aim of the study was to investigate the effect of statin use on the risk of CCA. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 41 publications
2
41
2
Order By: Relevance
“…Our findings are in line with the one previous study focusing on cholangiocarcinoma in Taiwan, which reported that the adjusted OR for statin use versus non-use for cholangiocarcinoma was 0.80 (95% CI 0.71 to 0.90) 27. The results are also consistent with studies that have demonstrated a decreased risk of gallstone disease,12–15 a risk factor for BTCs,28 especially GBC 1 2.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in line with the one previous study focusing on cholangiocarcinoma in Taiwan, which reported that the adjusted OR for statin use versus non-use for cholangiocarcinoma was 0.80 (95% CI 0.71 to 0.90) 27. The results are also consistent with studies that have demonstrated a decreased risk of gallstone disease,12–15 a risk factor for BTCs,28 especially GBC 1 2.…”
Section: Discussionsupporting
confidence: 92%
“…This is not consistent with the literature. Two previous case–control studies found consistently reduced risk for bile duct carcinoma (adjusted OR 0.87, 95% CI 0.75–1.01) and cholangiocarcinoma (adjusted OR 0.80, 95% CI 0.71–0.90) . The difference in the result between our study and two previous studies could be explained partly by the limited number of IBDC cases in the UK Biobank database.…”
Section: Discussioncontrasting
confidence: 89%
“…This retrospective cohort study used the data claims, a subset of the NHIRD, including the Registry of Beneficiaries, Registry of Catastrophic Illnesses Patient Database, and Longitudinal Health Insurance Database 2000. The details of similar databases utilized have been well described in previous studies . Diagnoses in the NHIRD were coded using the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM).…”
Section: Methodsmentioning
confidence: 99%